Economic development, democratic institutions, and repression in non-democratic regimes: Theory and evidence - Alexander Kemnitz; Martin Roessler (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
This paper analyzes the utilization of repression and democratic institutions by a non-democratic government striving for political power and private rents. We find that economic development has different impacts on policy choices, depending on whether it appears in the form of rises in income or in education: A higher income level reduces democracy, whereas more education leads to both more democracy and more repression. These theoretical findings are corroborated by panel data regressions.
urn:nbn:de:bsz:14-qucosa-221345
Keywords: C33; D72; K38; H11; O10; 330; Modernization Theory; Democracy; Repression; Non-democratic Government